The effect of humanistic leadership principles on the effectiveness of leading generation Z employees: A study in karanganyar - Rosiana, Intan Maharani; Utami, Eriska (Jurnal Mantik, 2025)
The study concentrates on the work system: humanistic leadership principles impact how well a leader can lead Generation Z—a highly skilled force in the operation of technology and harbor a particular preference for leadership. This is important because companies can improve employee performance, well-being, and productivity by understanding the leadership needs of Gen Z. The problem in this study is that there are limitations in understanding the extent to which humanistic leadership principles have a significant influence on the effectiveness of leadership in leading Generation Z employees. This research mostly focuses on ways that can be used to implement humanistic leadership to help Gen Z employees improve their performance and well-being. This study applies a quantitative approach as the main tool in collecting information through questionnaires, which are then analyzed using statistics. The Quantitative Method is used to measure how effective humanistic leadership is in Gen Z employees in Karanganyar by testing validity, reliability, normality, heterokedasticity, multicollinearity, F test, T test, determination coefficient test and multiple linear regression analysis using SPSS data processing tool. The results of the study showed that the variables of well-being, wisdom, empathy, and responsibility did not have a positive and significant impact on the effectiveness of leading Gen Z employees. Meanwhile, the variables of self-awareness, self-actualization, and fairness have a positive and significant impact on the effectiveness of Gen Z employees